Effects of marinating on the formation of polycyclic aromatic hydrocarbons (benzo[a]pyrene, benzo[b]fluoranthene and fluoranthene) in grilled beef meat - Afsaneh, Farhadian; Selamat, Jinap; Abas, Faridah; Sarker, Md. Zaidul Islam (Elsevier, 2012)
The study was conducted to investigate the effect of marinating on the generation of polycyclicaromatic hydrocarbons (benzo[a]pyrene, benzo[b]fluoranthene and fluoranthene) in grilled beef meat. Seven marinade treatments containing 1) basic marinade, which include sugar, water, onion, turmeric, lemon grass, salt, garlic, coriander and cinnamon, 2) basic–oil, 3) Commercial marinade. 4) basic–oil–lemon juice, 5) basic–lemon juice, 6) basic–oil–tamarind and 7) commercial–tamarind at four time intervals (0, 4, 8 and 12 h) were applied on meat samples before charcoal grilling. Tandem solid-phase extraction (SPE) was used to clean up the samples. A high performance liquid chromatography (HPLC) with fluorescence detector was used for PAHs analysis. The study showed significant (p < 0.05) reduction (70%) of PAH in beef samples treated with the acidic marinade (containing 1.2% lemon juice). The basic–lemon > basic > basic–oil–lemon > basic–oil was the best order of marinade treatment. The duration of marinating was not a significant (p > 0.05) factor in PAH reduction.